Fibre-based organic electrochemical transistors: principle, evaluation, and application - Yingying Huang; Zhijun Hu; Shouwen Zhu; Bo Fang (npj Flexible Electronics)
Abstract Organic electrochemical transistors (OECTs) are emerging organic semiconducting devices intensively used in biological detection, environmental monitoring, biomimetic electronics, and computing circuits, due to the high transconductance, low working voltage, and exceptional biocompatibility. Most reported OECTs are based on planar structures built by two dimensional (2D) semiconducting materials, which have found great challenges of rigid architecture, complicated fabrication, and small-scale production. To improve overall performance and extend the use of OECTs into wearables, integralization, miniaturization, and intellectualization, researchers have made intensive efforts to use 1D conducting polymer fibres as active channel for building new breed of fibre-based OECTs, namely F-OECTs. Here we present the research progress of F-OECTs along three lines: working principles, evaluation methods, and applications. Covering from P-type polymer to N-type polymer, various kinds of conducting polymers have been processed into channel materials of F-OECTs through mainstream wet spinning methods. The prepared F-OECTs have been widely used in in vivo recording, in vitro detection, neuromorphic sensing, and logical circuits. To conclude this review, we summarized current challenges in terms of performance optimization and material innovation, further suggesting possible solutions. This review could provide guidance for understanding the working principles of F-OECTs, designing high-performance F-OECTs, and fabricating advanced electronics.